2013
DOI: 10.3114/sim0021
|View full text |Cite
|
Sign up to set email alerts
|

The Botryosphaeriaceae: genera and species known from culture

Abstract: In this paper we give an account of the genera and species in the Botryosphaeriaceae. We consider morphological characters alone as inadequate to define genera or identify species, given the confusion it has repeatedly introduced in the past, their variation during development, and inevitable overlap as representation grows. Thus it seems likely that all of the older taxa linked to the Botryosphaeriaceae, and for which cultures or DNA sequence data are not available, cannot be linked to the species in this fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
700
0
29

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 779 publications
(778 citation statements)
references
References 176 publications
(495 reference statements)
49
700
0
29
Order By: Relevance
“…Several studies in recent years have highlighted the need to use additional phylogenetic markers to achieve accurate species identification (e.g. Bensch et al, 2012, Damm et al, 2012a, Damm et al, 2012b, Phillips et al, 2013and Wikee et al, 2013. In general, protein-coding genes have higher species resolution power due to their variable intron sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in recent years have highlighted the need to use additional phylogenetic markers to achieve accurate species identification (e.g. Bensch et al, 2012, Damm et al, 2012a, Damm et al, 2012b, Phillips et al, 2013and Wikee et al, 2013. In general, protein-coding genes have higher species resolution power due to their variable intron sequences.…”
Section: Introductionmentioning
confidence: 99%
“…A wide host range has also been reported (Sutton 1980). Recently, however, confirmed hosts of D. mutila have included only Chamaecyparis lawsoniana, Fraxinus spp., Malus spp., Populus spp., Taxus baccata and Vitis vinifera (Phillips et al 2013;Alves et al 2014). Molecular characterization of Polish isolates of this fungus were reported by Kraj et al (2013), who showed that isolates of D. mutila from F. excelsior in Poland were genetically very similar to isolates from other regions of the world.…”
Section: Occurrence Of Other Frequent Fungal Speciesmentioning
confidence: 99%
“…No entanto, pouco se conhece sobre a ocorrência e diversidade de espécies de Botryosphaeriaceae em plantas nativas do bioma Caatinga, localizado no Semiárido, e sobre a presença de fungos endofíticos nessas espécies, e muito menos sobre a sua importância como patógenos. O objetivo do presente estudo foi avaliar a patogenicidade de 74 isolados representando Espécies de Botryosphaeriaceae (Dothideomycetes) têm distribuição mundial, sendo encontradas em todas as regiões geográficas, incluindo áreas de clima tropical, temperado e até em ambiente marinho, com exceção das regiões polares (2,34,35,38). Já foram relatadas infectando plantas do grupo das monocotiledôneas, dicotiledôneas e gimnospermas, e até liquens (1).…”
unclassified